Continuity in geometric intuition between humans and monkeys - Jialin Li; Isabelle Boni; Logan R. Sandwick; Emily M. Sanford; Caroline M. DeLong; Li Wenjie; Margaret M. Henderson; Steven T. Piantadosi; Jessica F. Cantlon (Proceedings of the National Academy of Sciences, 2026)
Geometric intuition is regarded as a hallmark of human intelligence. Humans hold a unique advantage in recognizing geometric shapes with Euclidean features (e.g., parallelism, symmetry) and have more sophisticated geometric concepts than nonhuman primates. A popular explanation for this human distinctiveness is that humans rely on discrete, symbolic features to encode geometric shapes, while other primates depend only on continuous perceptual features. The current study challenges this view. We used a match-to-sample task to test whether monkeys share geometric representations with humans. We found that monkeys combined high-level perceptual representations with abstract symbolic representations like humans, suggesting a graded, quantitative continuity in geometric intuition across species rather than a categorical, qualitative divide. Importantly, monkeys showed stronger reliance on symbolic features when processing rotated geometric shapes than preschoolers did with unrotated shapes, indicating that what appears to be symbolic representation may largely emerge from rotation-invariant encoding. These results challenge the hypothesis of human uniqueness in geometric intuition and suggest that its origins in humans are rooted in abstractions shared with primates.